Electrolyte exposure time effects on structure, composition and biocompatibility of microarc oxidation coatings on Mg-Ca-Zn alloys - Marchenko, Ekaterina S.; Shishelova, Arina A.; Butyagin, Pavel I.; Gordienko, Ivan I.; Khrustalev, Anton P.; Arbuzova, Svetlana S.; Zhukov, Ilya A.; Baigonakova, Gulsharat A.; Volinsky, Alex A. (Surface and coatings technology)
The problem of using magnesium in medicine is biodegradation, which leads to the loss of the implant mechanical integrity before the bone tissue formation. Doping and subsequent coating deposition is an effective solution to this problem. This paper investigates the effects of electrolyte exposure time during micro-arc oxidation of the Mg-Ca-Zn alloy on its phase composition, biodegradation, and biocompatibility. As a result of micro-arc oxidation, a dense coating with a gradient structure is formed on the surface of the Mg-Ca-Zn alloy, consisting of amorphous and amorphous-nanocrystalline parts. The amorphous layers of the coating mainly consist of O, P, and Mg. The nanocrystalline layer is enriched in F, while the diffusion zone is enriched in O, F, and Mg. The coating has a porous structure typical for microarc oxidation. The nonlinear behavior of the diffraction pattern at small diffraction angles indicates the amorphous state of the coating. The amount of amorphous component is increasing with exposure time, indicating an increase in the coating thickness. Scratch testing with a diamond indenter tip indicates good coating adhesion. All coated Mg-Ca-Zn samples show a significant reduction in weight loss compared to the uncoated sample after 21 days in the culture medium. Surgical treatment of rabbit femurs with implants made from coated Mg-Ca-Zn samples demonstrated high biocompatibility. Clinical evaluation of the results showed a complete absence of purulent-inflammatory complications in all animals during the first 28 days after implantation.